Prioritization schema for immunotherapy clinical trials in glioblastoma. (2nd June 2016) - Hodges, Tiffany R.; Ferguson, Sherise D.; Caruso, Hillary G.; Kohanbash, Gary; Zhou, Shouhao; Cloughesy, Timothy F.; Berger, Mitchel S.; Poste, George H.; Khasraw, Mustafa; Ba, Sujuan; Jiang, Tao; Mikkelson, Tom; et al.
ABSTRACT: Background : Emerging immunotherapeutic strategies for the treatment of glioblastoma (GBM) such as dendritic cell (DC) vaccines, heat shock proteins, peptide vaccines, and adoptive T-cell therapeutics, to name a few, have transitioned from the bench to clinical trials. With upcoming strategies and developing therapeutics, it is challenging to critically evaluate the practical, clinical potential of individual approaches and to advise patients on the most promising clinical trials. Methods : The authors propose a system to prioritize such therapies in an organized and data-driven fashion. This schema is based on four categories of factors: antigenic target robustness, immune-activation and -effector responses, preclinical vetting, and early evidence of clinical response. Each of these categories is subdivided to focus on the most salient elements for developing a successful immunotherapeutic approach for GBM, and a numerical score is generated. Results : The Score Card reveals therapeutics that have the most robust data to support their use, provides a reference prioritization score, and can be applied in a reiterative fashion with emerging data. Conclusions : The authors hope that this schema will give physicians an evidence-based and rational framework to make the best referral decisions to better guide and serve this patient population.